Prinsip-Prinsip Pendidikan Islam : Sebuah Studi Pustaka - Sultan, Sultan; Syahrul, Syahrul; Damayanti, Ina (CV. Creative Tugu Pena, 2024)
The research aims to analyze the basis and objectives of Islamic education. The type of research used is library research, with research approaches namely a sociological educational approach and a normative theological approach. The results of the research show that the principles of Islamic education cannot be separated from the purpose of human life, namely to become servants who are devout, obedient and obedient to the commands of Allah SWT. and stay away from all His prohibitions. To achieve the goals of Islamic education, the principles of Islamic education are needed. Among the existing principles of Islamic education, the most important of them is the universal principle, namely the principle that shows the content of Islamic teachings covers all aspects, this makes it possible to study it using an inter, multi and transdisciplinary approach, then the principle of balance emphasizes that Islamic education builds a balanced mindset between the physical and the spiritual, between the worldly and the everyday, next is the principle of simplicity showing that Islamic education teaches an attitude of wasathan (middle) and moderation. Keywords: Principles of Islamic Education, Islamic Education, Sociological Educational Approach